Qual a percepção dos programadores sobre as ferramentas de refatoração? um estudo de replicação - COSTA, Marcos Almeida da (2019)
In this paper, we present a study of the replication of the work (PINTO; KAMEI, 2013) that seeks to understand the behavior of developers through data extracted from the Stack Overflow platform on subjects related to software refactoring. In addition to updating this study, we also seek to understand possible changes in the behavior of platform users in relation to refactoring tools. We analyzed the work of other authors who refer to the theme to enrich the analysis of the data collected.